Five functional domains associated with gait performance in Parkinson’s disease and lateral trunk flexion - Ota, Keisuke; Mani, Hiroki; Nochimura, Keita; Nakashiro, Yuichi; Hamada, Shinsuke; Moriwaka, Fumio (Frontiers in Neurology, 2025)
BackgroundLateral trunk flexion (LTF) is a common symptom of Parkinson’s disease (PD). The sensory re-weighting system and sensory-motor function are poor in patients with PD and LTF, and this may cause gait impairment. However, the specific characteristics of gait impairment in patients with PD and LTF remain unclear. The aim of this study was to compare the characteristics of the gait functional domains between participants with PD with and without LTF.MethodsFifty-eight patients with PD and Hoehn–Yahr grade 2–3 LTF were divided into two groups: the LTF group (n = 22) and the No LTF group (n = 36). The Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS)-Part III score and subjective visual vertical (SVV) angle were measured. The participants walked with a motion sensor on a straight 20 m path at a comfortable speed. Fifteen gait variables (10 gait cycles) were evaluated and categorized into pace, rhythm, asymmetry, variability, and postural control functional domains and were compared between groups.ResultsThe LTF angle, SVV angle; MDS-UPDRS-Part III total, rigidity, and axial scores; and the coefficients of variance for step length, step time, and stance time were significantly higher in the LTF group than in the No LTF group. No other significant differences were observed between the groups.ConclusionParticipants with PD and Hoehn–Yahr severity 2–3 LTF had greater gait variability than those without LTF, but maintained similar pace, rhythm, asymmetry, and postural control domains. Patients with PD and LTF may develop abnormal neural networks causing greater gait variability.